(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2022)
This article describes the role of investment in ensuring high economic growth, as well as investment policy inUzbekistan and the implementation of projects to restructure the economy, modernize industries, technical andtechnological renewal.